A framework for sharing knowledge in product development by e-collaboration through project management - Mohammadjafari Dr, M.; Ahmed, S.; Zawiah Md, S.; Zayandehroodi, H. (2012)
In this study, the author has purposed electronic collaboration (E-collaboration) through a project manager between different departments in a factory can create a favorable environment to development the projects in terms of time and cost. In fact, the E-collaboration is a tool in hands of project managers. For this concept the author purposes, a conceptual model for sharing knowledge, which support development product. The model uses four factors, namely, design, planning, procurement and production. In addition, these factors consist of several items separately: For design department, there are four categories: (1) standard materials (2) teamwork (3) expected level of production (4) process restrictiveness. For planning department, there are three categories: (1) schedules (2) Inventory control (3) Receive progress reports. For the procurement department, there are three categories: (1) information gathering (2) background review (3) negotiation. For production department, there are two categories: (1) check on the incoming raw materials (2) change volume of production. The performance of the conceptual model tested in terms of some objectives. This test has done by interview with 20 project managers in electronic industry in Iran. The result indicated the model has accuracy for development new products in conditions of time and cost.